One Adaptive Synchronization Approach for Fractional-Order Chaotic System with Fractional-Order 1<q<2 - Ping Zhou; Rongji Bai (The Scientific World Journal)
Based on a new stability result of equilibrium point in nonlinear fractional-order systems for fractional-order lying in 1<q<2, one adaptive synchronization approach is established. The adaptive synchronization for the fractional-order Lorenz chaotic system with fractional-order 1<q<2 is considered. Numerical simulations show the validity and feasibility of the proposed scheme.